Inorganic salt phase change material as well as preparation method and application thereof
By adding a nucleating agent and thermal filler to the inorganic salt phase change material to form a covering film, the problem of thermal enthalpy value attenuation of the phase change material is solved, and the stability and efficiency of the heat pump system are improved.
Patent Information
- Application Number
- CN202411369732.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-07
AI Technical Summary
Phase change materials are prone to attenuation of thermal enthalpy during frequent melting and crystallization, resulting in a decrease in the energy storage efficiency of the heat pump system.
Using inorganic salt phase change material compositions, including inorganic hydrated salts, nucleating agents, co-nucleating agents, thickening agents and thermal fillers, a covering film is formed to reduce moisture evaporation and improve crystalline form by specific component ratios and treatment methods. Growth and increase the enthalpy value.
It effectively reduces the thermal enthalpy attenuation of inorganic salt phase change materials, improves its service life and heat storage capacity, and enhances the stability and efficiency of the heat pump system.
Smart Images

Figure CN119264876A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of energy storage materials, and in particular to an inorganic salt phase change material and a preparation method and application thereof. Background Art
[0002] Phase change energy storage is a technology that uses phase changes (solid-liquid, gas-liquid) of materials to store energy. The heating process involves two processes: sensible heat storage and latent heat storage. During the latent heat storage process, the material temperature is almost constant. Compared with water that only uses sensible heat to store heat, phase change materials have higher heat storage capacity. Therefore, phase change energy storage technology is introduced into the heat pump system, and a phase change heat storage unit suitable for heat pumps is designed. The energy storage density of phase change materials can reach twice that of water (10℃~65℃), and the volume of the heat storage unit using phase change materials can be reduced to 50% of the volume of the heat storage unit using water heat storage. Phase change materials have very high application advantages in heat pump systems.
[0003] In the energy storage process, the phase change material absorbs heat from the heat source; in the heat release process, the low-temperature domestic water flows through the high-power heat exchanger to exchange heat with the phase change material to achieve instant hot water. In the frequent energy storage and heat release processes of the phase change material, the phase change material repeatedly melts and crystallizes, which easily leads to the decay of the thermal enthalpy value of the phase change material, and then the decay of the thermal enthalpy value of the phase change material. Summary of the invention
[0004] The embodiments of the present application provide an inorganic salt phase change material and a preparation method and application thereof, which can solve the problem that the phase change material is prone to thermal enthalpy decay during frequent melting-crystallization processes.
[0005] In a first aspect, the present invention provides an inorganic salt phase change material composition, wherein the composition comprises the following components:
[0006] Inorganic hydrated salt A 89.0wt.%~92.5wt.%, nucleating agent 2.0wt.%~5.0wt.%, auxiliary nucleating agent 0.4wt.%~1.0wt.%, thickener 0.2wt.%~2.7wt.%, thermal conductive filler 1.5wt.~5.0wt.%;
[0007] Wherein, the nucleating agent is selected from at least one of sodium salt, strontium salt and metal oxide, and the auxiliary nucleating agent is selected from at least one of non-metallic mineral materials.
[0008] In some embodiments, based on the total weight of the composition, the composition includes the following components: 91.0wt.% to 92.5wt.% of inorganic hydrated salt A, 2.5wt.% to 4.5wt.% of nucleating agent, 0.5wt.% to 0.8wt.% of co-nucleating agent, 0.8wt.% to 1.2wt.% of thickener, and 2.0wt.% to 3.0wt.% of thermal conductive filler.
[0009] In some embodiments, based on the total weight of the composition, the weight percentage of the inorganic hydrated salt A is f, the weight percentage of the nucleating agent is m, and the weight percentage of the auxiliary nucleating agent is n; the composition satisfies at least one of the following conditions:
[0010] (1) 20.56 ≤ f / (m + n) ≤ 23.13;
[0011] (2)3.5≤m / n≤35.0.
[0012] In some embodiments, the inorganic hydrated salt A is selected from at least one of sodium acetate trihydrate, magnesium nitrate hexahydrate, potassium acetate monohydrate, sodium thiosulfate pentahydrate, sodium sulfate decahydrate, calcium nitrate tetrahydrate, and magnesium sulfate pentahydrate.
[0013] In some embodiments, the sodium salt of the nucleating agent is selected from at least one of disodium hydrogen phosphate dodecahydrate, sodium pyrophosphate, sodium carbonate, and disodium hydrogen phosphate heptahydrate; the strontium salt of the nucleating agent is selected from at least one of strontium chloride hexahydrate, strontium acetate, strontium carbonate, and strontium nitrate; the metal oxide of the nucleating agent is selected from at least one of magnesium oxide, aluminum oxide, iron oxide, and ferrosoferric oxide.
[0014] In some embodiments, the non-metallic mineral material of the nucleating agent is selected from at least one of mica, montmorillonite, quartz, expanded perlite, talc, calcite, and feldspar; the particle size Dv of the non-metallic mineral material of the nucleating agent is 50 Meet 850μm≤Dv 50 ≤1500μm.
[0015] In some embodiments, the thickener is selected from at least one of cyclodextrin, chitosan, xanthan gum, sodium carboxycellulose, and soluble starch;
[0016] In some embodiments, the thermally conductive filler is selected from at least one of metal foam, expanded graphite, boron nitride, and molybdenum disulfide.
[0017] In a second aspect, the present application provides a method for preparing an inorganic salt phase change material, comprising: mixing the components in the inorganic salt phase change material composition as described above.
[0018] In some embodiments, mixing the components of the inorganic salt phase change material composition comprises the following steps:
[0019] Providing an inorganic hydrated salt A, heating the inorganic hydrated salt A to a preheating temperature, wherein the preheating temperature is greater than the melting point of the inorganic hydrated salt A, and performing a preheating treatment to obtain molten inorganic hydrated salt A;
[0020] Adding the nucleating agent to the molten inorganic hydrated salt A, and performing emulsification and ultrasonic treatment to obtain a mixture A;
[0021] Adding the nucleating agent and the thermal conductive filler to the mixture A for blending to obtain a mixture B;
[0022] Adding a thickener to the mixture B for thickening treatment to obtain a mixture C;
[0023] The mixture C is cooled and solidified to form an inorganic salt phase change material.
[0024] In some embodiments, the preheating treatment at least includes: a time of 2 hours to 3 hours, and a preheating temperature greater than the melting point of the inorganic hydrated salt A in the temperature range of 10° C. to 15° C.
[0025] In some embodiments, the emulsification ultrasonic treatment includes at least emulsification treatment and ultrasonic treatment, the stirring speed of the emulsification treatment is 5000r / min~8000r / min, the time is 10min~20min, the ultrasonic frequency of the ultrasonic treatment is 40kHz~60kHz, and the time is 20min~40min.
[0026] In some embodiments, the blending process at least includes: a vacuum degree of -0.15Mpa to -0.3Mpa, a stirring speed of 60r / min to 90r / min, and a time of 2h to 3h.
[0027] In some embodiments, the thickening treatment at least includes: adding the thickener to the mixture B in batches, with a stirring speed of 20r / min to 40r / min, for 1.5h to 2h, and the weight of the thickener added each time is 0.2% to 2.0% of the total weight of the thickener.
[0028] In a third aspect, the present application provides an inorganic salt phase change material, characterized in that the inorganic salt phase change material is prepared by the preparation method as described above.
[0029] In a fourth aspect, the present application provides a heat pump system, comprising an energy storage unit, wherein the energy storage unit comprises:
[0030] An energy storage shell having an energy storage cavity therein;
[0031] A heat exchange tube, disposed in the energy storage chamber; and
[0032] The phase change layer includes the inorganic salt phase change material as described above. The phase change layer is filled in the energy storage cavity and coated on the outer surface of the heat exchange tube to exchange heat with the heat exchange medium in the heat exchange tube.
[0033] Based on the inorganic salt phase change material and its preparation method and application of the embodiment of the present application, by adding a nucleating agent and selecting the content of each component in the inorganic salt phase change material composition within a suitable range, the nucleating agent is selected from at least one of the non-metallic mineral materials, which can provide a nucleation site for the crystallization of the inorganic hydrated salt A, and at the same time, a covering film can be formed on the surface of the inorganic salt phase change material to reduce the phase change enthalpy decay caused by water evaporation during the repeated operation of the inorganic hydrated salt. In the process of crystallization of the inorganic hydrated salt A, in addition to the nucleating agent that can promote the formation of crystal nuclei, the nucleating agent can also promote the growth of the crystal form, thereby achieving the effect of improving the decay of the enthalpy value of the inorganic salt phase change material and increasing the service life of the inorganic salt phase change material. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0035] Figure 1 This is a flow chart of a method for preparing an inorganic salt phase change material according to an embodiment of the present application;
[0036] Figure 2 This is a schematic structural diagram of a heat pump system according to an embodiment of the present application.
[0037] 10. Heat pump system; 20. Phase change layer;
[0038] 100. heat storage unit; 110. heat storage housing;
[0039] 200, heat exchange tube; 210, first heat exchange tube; 220, second heat exchange tube;
[0040] 300, heat source; 310, outlet end; 320, inlet end; 400, heating unit;
[0041] 500, reversing valve; 510, first reversing valve; 520, second reversing valve;
[0042] 610. Municipal water source; 620. Domestic water pipe. DETAILED DESCRIPTION
[0043] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0044] It should be noted that, in various aspects of the present application, for the same components in various aspects, the present application only describes one aspect once without repeating the description, which should not be understood by those skilled in the art as a limitation to the present application.
[0045] In the present application, unless otherwise stated, the room temperature or normal temperature refers to 25±2°C.
[0046] As mentioned above, the present application provides an inorganic salt phase change material composition, which can be used to prepare an inorganic salt phase change material. The inorganic salt phase change material can be used in a heat pump system to store and release heat.
[0047] The inorganic salt phase change material composition comprises the following components:
[0048] Inorganic hydrated salt A 89.0wt.%~92.5wt.%, nucleating agent 2.0wt.%~5.0wt.%, auxiliary nucleating agent 0.4wt.%~1.0wt.%, thickener 0.2wt.%~2.7wt.%, thermal conductive filler 1.5wt.~5.0wt.%;
[0049] The nucleating agent is selected from at least one of sodium salt, strontium salt and metal oxide, and the auxiliary nucleating agent is selected from at least one of non-metallic mineral materials.
[0050] In the present application, inorganic hydrated salt A is the main component of the inorganic salt phase change material that undergoes phase change, so that the inorganic salt phase change material has a suitable phase change temperature and a suitable thermal enthalpy value, and the nucleating agent is used to provide nucleation sites for the inorganic hydrated salt A so that the inorganic salt phase change material can be repeatedly melted-crystallized, and the thickener can increase the overall viscosity of the inorganic salt phase change material to inhibit the phase separation of the inorganic salt phase change material, so that the inorganic salt phase change material has good stability during frequent phase changes. The thermal conductivity of the inorganic hydrated salt A is relatively poor, and the inorganic salt phase change material is selected to also include a thermally conductive filler, which has good thermal conductivity and is used to improve the overall thermal conductivity of the inorganic salt phase change material for efficient heat transfer.
[0051] Since the inorganic hydrated salt A repeatedly melts and crystallizes during the frequent heat storage process and heat release process, the inorganic hydrated salt A itself undergoes multiple desorption and adsorption of water, and the high temperature in the molten state easily causes water to evaporate, which means that the effect of crystallization decreases, which easily leads to the thermal enthalpy value decay of the inorganic hydrated salt A, and then leads to the overall thermal enthalpy value decay of the inorganic salt phase change material. In the embodiment of the present application, by adding a nucleating agent, and selecting the content of each component in the inorganic salt phase change material composition to meet the scope of the present application, the nucleating agent is selected from at least one of the non-metallic mineral materials, and the non-metallic mineral material belongs to a water-insoluble heterogeneous nucleating agent, which can provide nucleation sites for the crystallization of the inorganic hydrated salt A, and at the same time can form a covering film on the surface of the inorganic salt phase change material, reducing the phase change thermal enthalpy decay caused by water evaporation of the inorganic hydrated salt during repeated working. In the process of crystallization of inorganic hydrated salt A, in addition to the nucleating agent that can promote the formation of crystal nuclei, the nucleating agent can also promote the growth of the crystal form, thereby achieving the effect of improving the thermal enthalpy value decay of the inorganic salt phase change material and improving the service life of the inorganic salt phase change material. When the weight percentage of inorganic hydrated salt A is lower than the lower limit of 89.0wt.%, the content of inorganic hydrated salt A is too low, resulting in a low energy storage density. When the weight percentage of inorganic hydrated salt A is higher than the upper limit of 92.5wt.%, the content of inorganic hydrated salt A is too high, increasing the risk of water evaporation. When the weight percentage of the nucleating agent is lower than the lower limit of 0.01wt.%, the content of the nucleating agent is too little, and the effect of promoting the growth of the crystal form is not achieved, and the protective film covered on the surface is not dense enough to achieve the effect of preventing water evaporation. When the weight percentage of the nucleating agent is higher than the upper limit of 1.0wt.%, the content of the nucleating agent is too high, and it is easy to cause blockage when the inorganic salt phase change material is filled in a small space, resulting in the difficulty of filling the inorganic salt phase change material.
[0052] In some embodiments, based on the total weight of the composition, the composition includes the following components: 91.0wt.% to 92.5wt.% of inorganic hydrated salt A, 2.5wt.% to 4.5wt.% of nucleating agent, 0.5wt.% to 0.8wt.% of co-nucleating agent, 0.8wt.% to 1.2wt.% of thickener, and 2.0wt.% to 3.0wt.% of thermal conductive filler. With this component, the thermal enthalpy decay rate of the inorganic salt phase change material is lower.
[0053] In some embodiments, based on the total weight of the composition, the weight percentage of the inorganic hydrated salt A is f, the weight percentage of the nucleating agent is m, and the weight percentage of the nucleating agent is n, wherein 20.56≤f / (m+n)≤23.13. Within this ratio range, the enthalpy decay rate of the inorganic salt phase change material is lower, and the supercooling degree is also lower, and after repeated melting-crystallization, it can still have good heat storage capacity.
[0054] In some embodiments, 3.5 ≤ m / n ≤ 35.0. The ratio of the nucleating agent to the co-nucleating agent is appropriate, and the co-nucleating agent can better promote the formation of crystallization and improve the crystal form, so as to achieve the effect of improving the heat storage capacity of the inorganic salt phase change material and extending the service life of the inorganic salt phase change material.
[0055] In the embodiments of the present application, the components in the inorganic salt phase change material composition are used in combination, and the prepared inorganic salt phase change material can maintain a phase change temperature close to the melting point of the inorganic hydrated salt A. Therefore, the inorganic hydrated salt A with a corresponding melting point can be selected according to the heat exchange temperature requirements of the heat pump system.
[0056] In some embodiments, the melting point Tm of the inorganic hydrated salt A satisfies the conditional formula 50°C ≤ Tm ≤ 65°C, and the inorganic hydrated salt A is selected from at least one of sodium acetate trihydrate, magnesium nitrate hexahydrate, and potassium acetate monohydrate.
[0057] In some embodiments, the melting point Tm of the inorganic hydrated salt A satisfies the conditional formula 35°C < Tm ≤ 50°C, and the inorganic hydrated salt A is selected from at least one of sodium thiosulfate pentahydrate, sodium sulfate decahydrate, calcium nitrate tetrahydrate, and magnesium sulfate pentahydrate.
[0058] In some embodiments, the sodium salt of the nucleating agent is selected from at least one of disodium hydrogen phosphate dodecahydrate (Na2HPO4·12H2O), sodium pyrophosphate (Na4P2O7), disodium hydrogen phosphate heptahydrate, and sodium carbonate; the strontium salt of the nucleating agent is selected from at least one of strontium chloride hexahydrate (SrCl2·6H2O), strontium acetate, strontium carbonate, and strontium nitrate; the metal oxide of the nucleating agent is selected from at least one of magnesium oxide, aluminum oxide, iron oxide, and magnetite. Selecting the above nucleating agent can provide crystal sites for the inorganic hydrated salt A, so that the inorganic salt phase change material can repeatedly melt and crystallize.
[0059] In some embodiments, the non-metallic mineral material of the co-nucleating agent is selected from at least one of mica, montmorillonite, quartz, expanded perlite, talc, calcite, and feldspar. By selecting the above co-nucleating agent, a thin film can be formed on the surface when the phase change material solidifies, reducing water evaporation caused by long-term high temperature, and promoting the crystal form growth after the formation of crystal nuclei of the inorganic hydrated salt A, thereby further improving the decay of the enthalpy value of the inorganic salt phase change material.
[0060] Among them, the co-nucleating agent exists as insoluble particles in the inorganic salt phase change material. In the embodiments of the present application, the particle size Dv 50 satisfies 850 μm ≤ Dv 50A nucleating agent with a particle size of ≤1500μm is added to mixture A. Within this particle size range, the nucleating agent can be evenly dispersed in the inorganic salt phase change material, and the thickener is used to stabilize the nucleating agent in the system to prevent sedimentation. At the same time, the excess nucleating agent will form a cavity-like film on the surface of the inorganic salt phase change material, which can prevent water evaporation and keep warm.
[0061] In some embodiments, the thickener is selected from at least one of cyclodextrin, chitosan, xanthan gum, sodium carboxycellulose, and soluble starch. The above thickener has good swelling properties and can improve the viscosity of the inorganic salt phase change material, thereby inhibiting the phase separation of the inorganic salt phase change material during the phase change process.
[0062] In some embodiments, the thermally conductive filler is selected from at least one of porous thermally conductive materials (metal foam, expanded graphite) and flaky thermally conductive materials (boron nitride, molybdenum disulfide). In the embodiments of the present application, the thermally conductive filler is selected from insoluble matter and exists as insoluble particles in the inorganic salt phase change material. The particle size Dv of the thermally conductive filler is 50 Meet 300μm≤Dv 50 ≤900μm. Within this particle size range, the components in the inorganic salt phase change material are evenly dispersed and have good stability, which prevents the local sedimentation of the thermal conductive filler, and the thermal conductive filler can play a more uniform and efficient thermal conductive role.
[0063] The second aspect of the present application provides a method for preparing an inorganic salt phase change material, comprising mixing the components in the inorganic salt phase change material composition as described above to prepare the inorganic salt phase change material.
[0064] In the embodiment of the present application, mixing the components of the inorganic salt phase change material composition includes the following steps:
[0065] Step S110, providing an inorganic hydrated salt A, heating the inorganic hydrated salt A to a preheating temperature, wherein the preheating temperature is greater than the melting point of the inorganic hydrated salt A, and performing a preheating treatment to obtain molten inorganic hydrated salt A.
[0066] Step S120, adding a nucleating agent to the molten inorganic hydrated salt A, performing emulsification and ultrasonic treatment, and obtaining a mixture A.
[0067] Step S130: adding a nucleating agent and a thermal conductive filler to the mixture A, and performing a blending process to obtain a mixture B.
[0068] Step S140: adding a thickener to mixture B to perform thickening treatment to obtain mixture C.
[0069] Step S150: Cooling and solidifying the mixture C to form an inorganic salt phase change material.
[0070] Among them, in steps S120 to S140, the temperature is maintained at the preheating temperature to keep the inorganic hydrated salt A in a molten state, so that the inorganic hydrated salt A and other components are uniformly dispersed.
[0071] In step S110, the inorganic hydrated salt A can be directly provided and directly heated to the preheating temperature for preheating treatment to obtain the molten inorganic hydrated salt A. In some other embodiments, the inorganic salt and deionized water can also be mixed according to the molar ratio of the inorganic salt to water in the inorganic hydrated salt A and heated to the preheating temperature, where the preheating temperature is higher than the melting point of the inorganic hydrated salt A, for preheating treatment to obtain the molten inorganic hydrated salt A.
[0072] In some embodiments, the preheating treatment at least includes: the time is 2 h to 3 h, and the temperature range where the preheating temperature is higher than the melting point of the inorganic hydrated salt A is 10°C to 15°C. Under this preheating condition, the inorganic hydrated salt A can be fully and uniformly melted to come into full and uniform contact with other components of the inorganic salt phase change material.
[0073] Among them, when the melting point Tm of the inorganic hydrated salt A satisfies the conditional formula 50°C ≤ Tm ≤ 65°C, correspondingly, the preheating temperature is 60°C to 75°C and the time is 2 h to 3 h; when the melting point Tm of the inorganic hydrated salt A satisfies the conditional formula 35°C < Tm ≤ 50°C, correspondingly, the preheating temperature is 45°C to 55°C and the time is 1.5 h to 2.5 h.
[0074] In some embodiments, the emulsification ultrasonic treatment at least includes: the stirring speed is 5000 r / min to 8000 r / min, the ultrasonic frequency is 40 kHz to 60 kHz, and the time is 20 min to 40 min. Under this emulsification ultrasonic treatment condition, the nucleating agent particles can be more fully and uniformly dispersed and scattered into the molten inorganic hydrated salt A. Among them, the emulsification ultrasonic treatment can include alternately performing emulsification treatment and ultrasonic treatment, performing emulsification treatment in an emulsification device, with the stirring speed of each emulsification treatment being 5000 r / min to 8000 r / min and the time being 10 min to 20 min, and performing ultrasonic treatment in an ultrasonic device, with the ultrasonic frequency of each ultrasonic treatment being 40 kHz to 60 kHz and the time being 20 min to 40 min, and the total time of the emulsification treatment and the ultrasonic treatment being 30 min to 60 min.
[0075] In some embodiments, the blending process at least includes: in a vacuum environment, the mixture A, the nucleating agent and the thermal conductive filler are mixed, and the vacuum degree is -0.15MPa to -0.3MPa, the stirring speed is 60r / min to 90r / min, and the time is 2h to 3h. Under the blending process conditions, the nucleating agent can fully contact with the inorganic hydrated salt A, and the vacuum environment can quickly rupture the bubbles formed during the preparation process, avoiding excessive gas in the mixture B that is not conducive to subsequent filling. In addition, due to the presence of negative pressure, the porous thermal conductive filler is a porous structure, which can fully absorb the components such as the nucleating agent, the nucleating agent, and the inorganic hydrated salt A in the composition, and form a better bridging effect between the thermal conductive fillers to better exert the thermal conductivity effect.
[0076] In some embodiments, the method for preparing the inorganic salt phase change material further comprises: crushing the nucleating agent and the thermal conductive filler respectively, and then adding them to the mixture A. The particle size Dv of the crushed nucleating agent is 50 Meet 850μm≤Dv 50 ≤1500μm, particle size Dv of thermal conductive filler 50 Meet 300μm≤Dv 50 ≤900 μm, so that the nucleating agent and the thermal conductive filler can be evenly dispersed in the mixture A. The pulverization process can be carried out by at least one of a ball mill and a high-speed pulverizer.
[0077] In some embodiments, the thickening treatment at least includes: adding the thickener to the mixture B in batches, and stirring at a speed of 20 r / min to 40 r / min for 1.5 h to 2 h, and the weight of the thickener added each time is 0.2% to 2.0% of the total weight of the thickener. The thickener is added in small amounts and multiple times to facilitate the swelling of the thickener and to evenly disperse it in the inorganic salt phase change material, so as to better improve the phase separation and prevent the thickener from agglomerating and causing uneven dispersion when a large amount of thickener is added.
[0078] like Figure 2 As shown, the present application also provides a heat pump system 10, which may include a water heater 100, and the water heater 100 may include an energy storage unit, the energy storage unit includes an energy storage shell 110, a heat exchange tube 200 and a phase change layer 20, and the phase change layer 20 includes the inorganic salt phase change material as described above. The energy storage shell 110 has an energy storage cavity inside, and the heat exchange tube 200 includes an inlet section, a middle section and an outlet section connected in sequence, the middle section is arranged in the energy storage cavity, and the inlet section and the outlet section extend from the energy storage cavity to the energy storage shell 110. The phase change layer 20 is filled in the energy storage cavity and coated on the middle section of the heat exchange tube 200 to exchange heat with the heat exchange medium in the heat exchange tube 200.
[0079] In some embodiments, the number of heat exchange tubes 200 of the energy storage unit is multiple. Figure 2As shown, there are two heat exchange tubes 200, one of which is a first heat exchange tube 210 and the other is a second heat exchange tube 220. The heat pump system 10 further includes a heat source unit 300, the inlet section of the first heat exchange tube 210 is connected to the outlet end 310 of the heat source unit 300, and the outlet section is connected to the inlet end 320 of the heat source unit 300, and the heat source unit 300 exchanges heat with the phase change layer 20 through the heat exchange medium in the first heat exchange tube 210.
[0080] The first heat exchange tube 210 and the second heat exchange tube 220 can be made of stainless steel independently. When the inorganic salt phase change material also includes a corrosion inhibitor, the first heat exchange tube 210 and the second heat exchange tube 220 can also include copper material.
[0081] like Figure 2 As shown, when the water heater 100 includes an energy storage unit, the inlet section of the second heat exchange tube 220 of the energy storage unit is connected to the municipal water source 610, and the outlet section is connected to the domestic water pipe 620. The heat storage unit 100 has a heat storage mode, a heat release mode and a mixed mode. Specifically, in the heat storage mode, the high-temperature heat exchange medium of the heat source 300 enters the first heat exchange tube 210 from the inlet section of the first heat exchange tube 210, and the inorganic salt phase change material absorbs the heat of the high-temperature heat exchange medium in the first heat exchange tube 210 and stores the heat, and the high-temperature heat exchange medium becomes a low-temperature heat exchange medium and flows back from the outlet section of the first heat exchange tube 210 to the inlet end 320 of the heat source 300; in the heat release mode, the low-temperature water flow supplied by the municipal water source 610 enters the second heat exchange tube 220 from the inlet section Heat pipe 220, the inorganic hydrated salt transfers heat to the low-temperature water flow in the second heat exchange tube 220, and the low-temperature water flow absorbs heat and becomes high-temperature water flow, which flows out from the outlet section of the second heat exchange tube 220 for user use; in the mixed mode, the high-temperature heat exchange medium of the heat source 300 enters the first heat exchange tube 210 from the inlet section of the first heat exchange tube 210, and at the same time, the low-temperature water flow supplied by the municipal water source 610 enters the second heat exchange tube 220 from the inlet section of the second heat exchange tube 220, the inorganic salt phase change material absorbs the heat of the high-temperature heat exchange medium in the first heat exchange tube 210 and transfers the heat to the low-temperature water flow in the second heat exchange tube 220 at the same time, the low-temperature water flow absorbs heat and becomes high-temperature water flow or medium-temperature water flow, which flows out from the outlet section of the second heat exchange tube 220 for user use.
[0082] The heat pump system 10 also includes a heating unit 400, a reversing valve 500 and connecting pipes connecting the various structures. The reversing valve 500 includes a first reversing valve 510. The first end of the first reversing valve 510 is connected to the outlet end 310 of the heat source 300, the second end is connected to the heating unit 400, and the third end is connected to the heat exchange pipe 200 of the heat storage unit 100. By switching the flow path of the first reversing valve 510, the outlet end 310 of the heat source 300 can be connected to at least one of the heating unit 400 and the heat storage unit 100 to provide high-temperature heat exchange medium to the heating unit 400 and the heat storage unit 100 accordingly. The number of heating units 400 may be multiple, and the reversing valve 500 may also include a second reversing valve 520. The second reversing valve 520 is arranged on the second end of the first reversing valve 510 and is connected to a connecting pipe connected to the multiple heating units 400. By switching the flow path of the second reversing valve 520, the second end of the first reversing valve 510 is connected to one or more of the multiple heating units 400, and then the heat source 300 is connected to one or more of the multiple heating units 400.
[0083] The following is a method for preparing an inorganic salt phase change material in combination with an embodiment and a comparative example. It will be understood by those skilled in the art that the preparation method described in this application is only an example, and any other suitable preparation method is within the scope of this application. In the following embodiments, unless otherwise specified, all raw materials used are commercially available.
[0084] In each embodiment and comparative example of the present application, the performance test method of the inorganic salt phase change material is as follows:
[0085] 1. Phase change temperature and supercooling test method
[0086] The phase change temperature is measured by the step cooling curve method: 100g of phase change material is placed in a high borosilicate glass bottle, a K-type thermocouple is inserted into the middle of the phase change material, and then the phase change material is heated to 20°C above the melting point of the inorganic hydrated salt and stabilized for 30 minutes. Then, it is placed in an environment 30°C below the melting point for natural cooling, and the temperature information of the phase change material changing with time is collected to obtain the temperature-time curve and the corresponding theoretical phase change temperature (T theory ) and the actual phase transition temperature (T actual ).
[0087] Theoretical phase transition temperature (T theory ) and the actual phase transition temperature (T actual ) is the supercooling degree (T sc ).
[0088] 2. Test method for thermal enthalpy decay rate after 2000 cycles
[0089] The initial unit mass enthalpy of the phase change material is measured by DSC equipment.
[0090] The phase change material is loaded into the cycle test device.
[0091] The melt-crystallization cycle is carried out as follows:
[0092] (1) Initial temperature 0°C, let stand for 5 minutes;
[0093] (2) Perform heating treatment at a heating rate of 5°C / min, a stop temperature of 80°C, and stand for 5 min;
[0094] (3) Cooling treatment was performed at a cooling rate of 5°C / min, an end temperature of 0°C, and the mixture was allowed to stand for 1 min.
[0095] Among them, the above steps (1)-(3) are the first melt-crystallization cycle, and then the steps (2)-(3) are a melt-crystallization cycle. After the phase change material has been melt-crystallized for 2000 times, the unit mass thermal enthalpy of the phase change material after 2000 cycles is measured by DSC equipment.
[0096] The calculation formula of the thermal enthalpy decay rate per unit mass is: H% = (1-△H n / △H0)×100%;
[0097] Among them, △H n is the unit mass enthalpy of the phase change material after n cycles, kJ / kg;
[0098] △H0 is the initial unit mass enthalpy of the phase change material, kJ / kg.
[0099] 3. Energy storage density test method
[0100] The density of phase change materials was measured by density meter. s ) and liquid density (р l );
[0101] The solid-state specific heat capacity C of phase change materials was measured by differential scanning calorimetry (DSC) using the MDSC method. ps and liquid specific heat C pl .
[0102] The initial unit mass enthalpy ΔH0 of the phase change material was measured by differential scanning calorimetry (DSC).
[0103] The energy storage density △Q is calculated according to the following formula:
[0104] △Q=р s ×(T actual -10)×C ps +(р s +р l ) / 2×△H0+р l× (65-Tactual )×C pl .
[0105] Example 1
[0106] This embodiment provides a method for preparing an inorganic hydrated phase change material, the method comprising the following steps:
[0107] (1) Preheating
[0108] According to the molar ratio of inorganic salt sodium acetate (CH3COONa) to deionized water being 1:3, 55.47 g of inorganic salt sodium acetate and 36.53 g of deionized water were weighed and mixed evenly, and heated to a preheating temperature of 75°C to obtain molten CH3COONa·3H2O.
[0109] Based on the total weight of the inorganic hydrated phase change material composition, the weight percentage of CH3COONa·3H2O is 92 wt.%.
[0110] (2) Emulsification ultrasonic treatment
[0111] At 70°C, 4 g of a nucleating agent, disodium hydrogen phosphate dodecahydrate, was added to molten CH3COONa·3H2O, and emulsified in an emulsifying device at a stirring speed of 6000 r / min for 15 min. Then, an ultrasonic treatment was performed in an ultrasonic device at a frequency of 55 kHz for 30 min to obtain a mixture A.
[0112] Wherein, based on the total weight of the inorganic hydrated phase change material composition, the weight percentage of disodium hydrogen phosphate dodecahydrate is 4 wt.%.
[0113] (3) Blending
[0114] At 70°C, the particle size Dv 50 0.8g nucleating agent mica and particle size Dv of 1000μm 50 2.0 g of 300 μm boron nitride, a thermally conductive filler, was added to mixture A, and the mixture was stirred evenly under the action of a vacuum stirrer to perform a blending treatment. The vacuum degree of the blending treatment was -0.3 MPa, the stirring speed was 80 r / min, and the time was 2.5 h to obtain mixture B.
[0115] Wherein, based on the total weight of the inorganic hydrated phase change material composition, the weight percentage of mica is 0.8 wt.%, and the weight percentage of boron nitride is 0.8 wt.%.
[0116] (4) Thickening treatment
[0117] At 70° C., a thickener, sodium carboxymethyl cellulose, was added to mixture B in three portions, with 1.2 g added each time. The mixture was stirred at a speed of 30 r / min and thickened for 1.5 h to obtain mixture C.
[0118] Wherein, based on the total weight of the inorganic hydrated phase change material composition, the weight percentage of sodium carboxymethyl cellulose is 1.2 wt.%.
[0119] (5) Cooling treatment
[0120] The mixture C is cooled to room temperature 25° C., and the mixture C solidifies to form an inorganic salt phase change material.
[0121] Examples 2 to 6, Examples 9 to 16, and Comparative Examples 1 to 4 are the same as Example 1 except that the contents of inorganic salt, deionized water, nucleating agent, nucleating aid, thermal conductive filler and thickener are adjusted as shown in Table 1.
[0122] Example 7 is the same as Example 1 except that the contents of inorganic salt, deionized water, nucleating agent, nucleating aid, thermal conductive filler and thickener are adjusted in each processing step as shown in Table 1, and the preheating temperature of step (1) is 60°C and the temperature of steps (2) to (4) is 55°C.
[0123] Example 8 is the same as Example 1 except that the contents of inorganic salt, deionized water, nucleating agent, nucleating aid, thermal conductive filler and thickener are adjusted in each processing step as shown in Table 1, and the preheating temperature of step (1) is 55°C and the temperature of steps (2) to (4) is 50°C.
[0124] The preparation parameters and performance parameters of Examples 1 to 16 and Comparative Examples 1 to 4 are shown in Table 1.
[0125]
[0126] It can be seen from Examples 1 to 16 and Comparative Examples 1 to 4 in Table 1 that by adding a water-insoluble nucleating agent to the inorganic salt phase change material composition and selecting the components of the inorganic salt phase change material composition within a suitable range, the enthalpy value of the obtained inorganic salt phase change material after 2000 cycles can still be maintained at a high level, the enthalpy value decay rate after 2000 cycles is ≤5%, and the supercooling and energy storage density are both within a suitable range. The inorganic salt phase change material in the embodiment of the present application can be used in a heat pump system and has good heat storage performance.
[0127] From Comparative Example 1 to Comparative Example 2, it can be seen that when the weight percentage of inorganic hydrated salt A is lower than the lower limit of 89.0wt.%, the content of inorganic hydrated salt A is too low, resulting in a low energy storage density at 10°C to 65°C. When the weight percentage of inorganic hydrated salt A is higher than the upper limit of 92.5wt.%, the content of inorganic hydrated salt A is too high, which increases the risk of water evaporation and is prone to phase separation. When the weight percentage of the nucleating agent is lower than the lower limit of 0.4wt.%, the content of the nucleating agent is too little, which does not promote the growth of the crystal form, and the protective film covered on the surface is not dense enough to prevent water evaporation. The enthalpy decay rate of the inorganic salt phase change material after 2000 cycles deteriorates. When the weight percentage of the nucleating agent is higher than the upper limit of 1.0wt.%, the content of the nucleating agent is too high, which is easy to cause blockage when the inorganic salt phase change material is filled in a small space, making it difficult to fill the inorganic salt phase change material.
[0128] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. An inorganic salt phase change material composition, characterized in that: The composition comprises the following components: Inorganic hydrated salt A 89.0wt.%~92.5wt.%, nucleating agent 2.0wt.%~5.0wt.%, auxiliary nucleating agent 0.4wt.%~1.0wt.%, thickener 0.2wt.%~2.7wt.%, thermal conductive filler 1.5wt.~5.0wt.%; Wherein, the nucleating agent is selected from at least one of sodium salt, strontium salt and metal oxide, and the auxiliary nucleating agent is selected from at least one of non-metallic mineral materials.
2. The composition according to claim 1, characterized in that Based on the total weight of the composition, the composition comprises the following components: Inorganic hydrated salt A 91.0wt.% to 92.5wt.%, nucleating agent 2.5wt.% to 4.5wt.%, auxiliary nucleating agent 0.5wt.% to 0.8wt.%, thickener 0.8wt.% to 1.2wt.%, thermal conductive filler 2.0wt.% to 3.0wt.%.
3. The composition according to claim 1, characterized in that Based on the total weight of the composition, the weight percentage of the inorganic hydrated salt A is f, the weight percentage of the nucleating agent is m, and the weight percentage of the auxiliary nucleating agent is n; the composition satisfies at least one of the following conditions: (1) 20.56 ≤ f / (m + n) ≤ 23.13; (2)3.5≤m / n≤35.
0.
4. The composition according to claim 1, characterized in that The inorganic hydrated salt A is selected from at least one of sodium acetate trihydrate, magnesium nitrate hexahydrate, potassium acetate monohydrate, sodium thiosulfate pentahydrate, sodium sulfate decahydrate, calcium nitrate tetrahydrate, and magnesium sulfate pentahydrate.
5. The composition according to claim 1, characterized in that The sodium salt of the nucleating agent is selected from at least one of disodium hydrogen phosphate dodecahydrate, sodium pyrophosphate, sodium carbonate, and disodium hydrogen phosphate heptahydrate; The strontium salt of the nucleating agent is selected from at least one of strontium chloride hexahydrate, strontium acetate, strontium carbonate, and strontium nitrate; The metal oxide of the nucleating agent is selected from at least one of magnesium oxide, aluminum oxide, iron oxide and ferrosoferric oxide.
6. The composition according to claim 1, characterized in that The non-metallic mineral material of the nucleating agent is selected from at least one of mica, montmorillonite, quartz, expanded perlite, talc, calcite and feldspar; The particle size Dv of the non-metallic mineral material of the nucleating agent 50 Meet 850μm≤Dv 50 ≤1500μm.
7. The composition according to claim 1, characterized in that The thickener is selected from at least one of cyclodextrin, chitosan, xanthan gum, sodium carboxycellulose, and soluble starch; The thermally conductive filler is selected from at least one of metal foam, expanded graphite, boron nitride and molybdenum disulfide.
8. A method for preparing an inorganic salt phase change material, characterized in that: include: The components of the inorganic salt phase change material composition according to any one of claims 1 to 7 are mixed.
9. The preparation method according to claim 8, characterized in that: Mixing the components of the inorganic salt phase change material composition comprises the following steps: Providing an inorganic hydrated salt A, heating the inorganic hydrated salt A to a preheating temperature, wherein the preheating temperature is greater than the melting point of the inorganic hydrated salt A, and performing a preheating treatment to obtain molten inorganic hydrated salt A; Adding the nucleating agent to the molten inorganic hydrated salt A, and performing emulsification and ultrasonic treatment to obtain a mixture A; Adding the nucleating agent and the thermal conductive filler to the mixture A for blending to obtain a mixture B; Adding a thickener to the mixture B for thickening treatment to obtain a mixture C; The mixture C is cooled and solidified to form an inorganic salt phase change material.
10. The preparation method according to claim 9, characterized in that: The preheating treatment at least includes: a time of 2h to 3h, a preheating temperature greater than the melting point of the inorganic hydrated salt A in the temperature range of 10°C to 15°C; The emulsification ultrasonic treatment at least includes emulsification treatment and ultrasonic treatment, the stirring speed of the emulsification treatment is 5000r / min-8000r / min, the time is 10min-20min, the ultrasonic frequency of the ultrasonic treatment is 40kHz-60kHz, and the time is 20min-40min; The blending process at least includes: vacuum degree of -0.15Mpa to -0.3Mpa, stirring speed of 60r / min to 90r / min, and time of 2h to 3h; The thickening treatment at least includes: adding the thickener to the mixture B in batches, with a stirring speed of 20r / min to 40r / min, for 1.5h to 2h, and the weight of the thickener added each time is 0.2% to 2.0% of the total weight of the thickener.
11. An inorganic salt phase change material, characterized in that: The inorganic salt phase change material is prepared by the preparation method described in any one of claims 8 to 10.
12. A heat pump system, characterized in that: An energy storage unit is included, wherein the energy storage unit includes: An energy storage shell having an energy storage cavity therein; A heat exchange tube, disposed in the energy storage chamber; and The phase change layer comprises the inorganic salt phase change material according to claim 11, wherein the phase change layer is filled in the energy storage cavity and coated on the outer surface of the heat exchange tube to exchange heat with the heat exchange medium in the heat exchange tube.
Citation Information
Cited By
Inorganic salt phase change material and preparation method therefor and use thereof
WO2026067090A1